2020
DOI: 10.1111/1556-4029.14504
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Sexual Murderers: Examination and Classification of the Crime‐Commission Process

Abstract: This study aims to empirically explore the crime‐commission process of juvenile sexual homicide offenders (SHOs). First, a comparison between the crime‐commission process of juvenile and adult SHOs is undertaken, while as a second step, this study also provides an empirical classification specific to juvenile SHOs. The sample used in this study consists of 55 juvenile SHOs and 281 adult SHOs. A sequential binomial regression was used to compare at the multivariate level the two groups of offenders, while a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Previous studies have found that some sexual homicide offenders of male victims targeted specifically their victims and followed a revenge process or began a consensual sexual activity that negatively escalated into violence (Beauregard & Proulx, 2007; Geberth, 1996). Studies also indicated that sexual homicide offenders sometimes focused specifically on young male victims (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014). Finally, previous findings indicated that sometimes the main motivation for the crime was a financial gain and sexual acts were committed concomitantly (Geberth, 1996), while in other situations sexual homicide offenders were mainly motivated by the penetration of the victim as well as sexual sadism (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that some sexual homicide offenders of male victims targeted specifically their victims and followed a revenge process or began a consensual sexual activity that negatively escalated into violence (Beauregard & Proulx, 2007; Geberth, 1996). Studies also indicated that sexual homicide offenders sometimes focused specifically on young male victims (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014). Finally, previous findings indicated that sometimes the main motivation for the crime was a financial gain and sexual acts were committed concomitantly (Geberth, 1996), while in other situations sexual homicide offenders were mainly motivated by the penetration of the victim as well as sexual sadism (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Studies also indicated that sexual homicide offenders sometimes focused specifically on young male victims (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014). Finally, previous findings indicated that sometimes the main motivation for the crime was a financial gain and sexual acts were committed concomitantly (Geberth, 1996), while in other situations sexual homicide offenders were mainly motivated by the penetration of the victim as well as sexual sadism (Beauregard & Proulx, 2007; Chopin & Beauregard, 2020a; Geberth, 1996, 2010, 2014). We used a total of five dichotomous (0 = no; 1 = yes) variables: (1) offender targeted his victim, (2) victim was less than 16 years old, (3) intrusive sexual acts with a penis, (4) offender took items from victim/offense, and (5) sexual sadism (SADSEX-SH scale).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crime pattern of anger sexual murderers is mainly characterized by a disproportionate level of violence associated with feelings of anger that occurred during the pre-crime phase. Methods of killing used by angry offenders are asphyxiation and strangulation, and while they are more likely to perpetrate overkill behaviors, they are less likely to move the victim's body (Beauregard & Proulx, 2002;Beech et al, 2005;Beech et al, 2001;Chopin & Beauregard, 2020b;Kocsis et al, 2002;Stefanska et al, 2015). Angry sexual murderers present problems of substance abuse (i.e., alcohol, drugs), previous criminal conviction for non-violent and non-sexual offenses (e.g., burglaries).…”
Section: What Are the Main Sexual Murderers' Typologies?mentioning
confidence: 99%
“…It has also been established that the crime-commission process followed by juvenile sexual murderers presents specificities depending on the young age of the offenders (e.g., lack of maturity, limited mobility, etc.) (Chopin & Beauregard, 2020b).…”
Section: What Are the Main Sexual Murderers' Typologies?mentioning
confidence: 99%